2007
DOI: 10.1246/bcsj.80.595
|View full text |Cite
|
Sign up to set email alerts
|

Nitroso and Azo Compounds in Modern Organic Synthesis: Late Blooming but Very Rich

Abstract: The catalytic enantioselective oxidation is an extremely important process in organic synthesis and numbers of effort to improve this process have been reported so far. Although nitroso and azo compounds are attractive tools for hydroxylation and amination of organic compounds, no reports on a catalytic asymmetric version of these reactions had been reported until recently. The main issues were their high and unique reactivities. In this review, we would like to introduce the recent advances in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 161 publications
(57 citation statements)
references
References 100 publications
2
50
0
5
Order By: Relevance
“…[41] The observed stereochemistry can be rationalized by an analogous transition-state model in which nitrosobenzene approaches the Si face of the s-cis-enamine, as directed by the triflamide group (Figure 1c). Because activation of nitrosobenzene by strong acids such as carboxylic acid and tetrazole is necessary to obtain the aminoxylation product, [42] only a combination of the s-cis-enamine and nitrosobenzene activated on the Si face of the enamine can provide the S isomer. This observation strongly suggests the existence of the s-cis-enamine intermediate in the Mannich and aldol reactions catalyzed by (S)-3 reported herein.…”
Section: A C H T U N G T R E N N U N G [Mol %]mentioning
confidence: 99%
“…[41] The observed stereochemistry can be rationalized by an analogous transition-state model in which nitrosobenzene approaches the Si face of the s-cis-enamine, as directed by the triflamide group (Figure 1c). Because activation of nitrosobenzene by strong acids such as carboxylic acid and tetrazole is necessary to obtain the aminoxylation product, [42] only a combination of the s-cis-enamine and nitrosobenzene activated on the Si face of the enamine can provide the S isomer. This observation strongly suggests the existence of the s-cis-enamine intermediate in the Mannich and aldol reactions catalyzed by (S)-3 reported herein.…”
Section: A C H T U N G T R E N N U N G [Mol %]mentioning
confidence: 99%
“…[188] Either, the reduction from the nitro group to the nitroso (which is in fact an insitu reduction of the nitro group to the amine followed by an oxidation to the nitroso), [209] or a stepwise procedure including the reduction to the amine and subsequent oxidation to the nitroso. [189] [210] Both strategies had in common the problem of the delicate oxidation, in order not to over oxidizing to the nitro group.…”
Section: Scheme 17mentioning
confidence: 99%
“…A series of reactions with phosphine ligands showed clearly that electron-deficient phosphine ligands gave the O adduct 3 a preferentially ( Table 2, entries 1-4). Encouraged by these results, we tested other electrondeficient ligands and found that PPh(OPh) 2 and P(OPh) 3 gave 3 a with good selectivity (Table 2, entries 5, 6, and 8). Moreover, when 10 mol % of P(OPh) 3 was used, 3 a was obtained almost exclusively (Table 2, entry 9).…”
mentioning
confidence: 88%